The essential role of mental imagery in cognitive behaviour therapy: What is old is new again. (2nd May 2019) - Saulsman, Lisa M.; Ji, Julie L.; McEvoy, Peter M.
Abstract: Objective: The aim of this review is to highlight the important role of mental imagery in contemporary cognitive behaviour therapy (CBT). Method: In this narrative review, we define mental imagery based on cognitive science research, present the rationale for the incorporation of mental imagery within CBT, and outline four key applications of mental imagery within CBT practice (i.e., imagery‐enhanced thought records, imagery‐enhanced behavioural experiments, imaginal facilitation of behaviour change, and imagery rescripting), including emerging research supporting these varied applications. Results: Mental imagery is highly relevant to CBT practice because (a) it is a transdiagnostic cognitive maintaining factor of psychopathology; (b) it promotes cognitive specificity when working with clients; and (c) the emotional amplification properties of mental imagery, and its impacts on motivation and behaviour, make imagery a powerful facilitator of cognitive, affective, and behavioural change. Emerging research is promising regarding the potential for imagery to enhance treatment outcomes. However, further research is required to guide clinicians regarding how to best facilitate imagery interventions to maximise outcomes. Conclusions: Imagery‐focused interventions are an essential part of a CBT practitioner's therapeutic repertoire. Mental imagery has the capacity to bring CBT to life, facilitating conditions important for engaging and effective psychotherapy.